International delegates - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows people marching in the National March on Washington for Lesbian and Gay Rights. Two men in front hold up a banner that reads, "International delegates". Someone else is carrying the Canadian flag. The United States Capital is visible in the background at far right.